2014
DOI: 10.1002/gcc.22206
|View full text |Cite
|
Sign up to set email alerts
|

ZFP36‐FOSB fusion defines a subset of epithelioid hemangioma with atypical features

Abstract: Epithelioid hemangioma (EH) is a benign neoplasm with distinctive vasoformative features, which occasionally shows increased cellularity, cytologic atypia, and/or loco-regional aggressive growth, resulting in challenging differential diagnosis from malignant vascular neoplasms. Based on two intra-osseous EH index cases with worrisome histologic features, such as the presence of necrosis, RNA sequencing was applied for possible fusion gene discovery and potential subclassification of a novel atypical EH subset.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
185
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(189 citation statements)
references
References 31 publications
4
185
0
Order By: Relevance
“…Although our group has recently identified recurrent ZFP36-FOSB fusions in a small subset of EH with atypical features 10 , the underlying genetic alteration responsible for most EHs remains elusive. In this study, we took advantage of an index case with available frozen tissue, which was subjected to RNA sequencing and FusionSeq analysis, to identify novel gene rearrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our group has recently identified recurrent ZFP36-FOSB fusions in a small subset of EH with atypical features 10 , the underlying genetic alteration responsible for most EHs remains elusive. In this study, we took advantage of an index case with available frozen tissue, which was subjected to RNA sequencing and FusionSeq analysis, to identify novel gene rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Kimura disease), while at the other end of the spectrum (cellular EH) with malignant epithelioid vascular tumors, such as epithelioid hemangioendothelioma (EHE) and epithelioid angiosarcoma (AS). Moreover, the distinction from malignant lesions is further complicated by the aggressive clinical presentation of intra-osseous EH with destructive growth and/or multifocality, or by the presence of atypical histologic features with increased mitotic activity and necrosis 2, 3, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…20 The epithelioid hemangiomas with this finding were more common on the penis and had atypical features, including solid growth, less inflammation, and necrosis. Conventional epithelioid hemangiomas were not found to have this cytogenetic abnormality, suggesting that what has been collectively described as epithelioid hemangioma may represent a molecularly diverse group of tumors with morphologic overlap.…”
Section: Challenging Epithelioid Vascular Tumorsmentioning
confidence: 95%
“…[21][22][23] The vascular component of Kimura disease has relatively flattened, attenuated endothelial cells compared with the plumper, often "tomb-stoning" endothelial cells in epithelioid hemangioma. 20,24 The distinct clinical presentation of Kimura disease, including Asian men with lymphadenopathy, peripheral eosinophilia, increased serum immunoglobulin E (IgE), and possibly proteinuria and nephrotic syndrome, also is useful when clinical information is available.…”
Section: Challenging Epithelioid Vascular Tumorsmentioning
confidence: 99%
“…Huang et al [58] have demonstrated FOS rearrangement in a third of EH, with increased prevalence in intraosseous (59% of intraosseous EH) and cellular EH (70% of all FOS-rearranged EH). In a study by Antonescu et al [59] , FOSB rearrangement was observed in 20% of EH. Morphologically, tumors with FOSB rearrangement contained solid areas, increased cellularity, and nuclear pleomorphism.…”
Section: Vascular Tumorsmentioning
confidence: 99%